A Keynesian fourth paradigm: Re-embedding the market and the state for a new American grand strategy - English, Vincent (International Journal of Economics, Business and Management Studies, 2025)
This paper proposes a Keynesian ‘fourth paradigm’ for American grand strategy to overcome the stalemate between realism, liberalism and constructivism in International Relations. Drawing on close reading of Keynes’s major works, contemporary IR scholarship and recent policy debates, the article combines intellectual history with analytical synthesis to reconstruct Keynes’s international thought and translate it into a coherent strategic framework for the United States in the twenty-first century. The analysis shows that a Keynesian paradigm re-embeds markets within social and political institutions, treats economic stability and full employment as preconditions for durable peace, foregrounds uncertainty and ‘animal spirits’ in state decision-making, and advances a model of managed multilateralism that constrains both surplus and deficit states; it also demonstrates how this perspective exposes and resists the ‘military-narrational complex’ that privileges dramatic war stories over prudential statecraft. The article further finds that a Keynesian grand strategy would orient US policy towards reform of global economic governance, construction of a new embedded liberalism at home and abroad, and a pragmatic, cooperative internationalism that prioritises economic statecraft and narrative scepticism over military dominance. These findings suggest that thinking more like Keynes could help American policymakers design a grand strategy that is both analytically richer and more practically suited to managing great-power rivalry, climate change, financial instability, and populist backlash in a turbulent world.